2021
DOI: 10.47162/rjme.61.3.21
|View full text |Cite
|
Sign up to set email alerts
|

Successful management of spontaneous bone regeneration after jaws cystectomy using PRGF approach; case series

Abstract: In the jaws, the healing process of bone defects occurs differently compared with other anatomical sites where healing is done by the formation of scar tissue. This is due to physiological bone remodeling and continuous bone resorption and apposition. In the case of large cysts, there is an increased risk of postoperative infection due to the retraction of the blood clot on the bony walls. The use of plasma rich in growth factors (PRGF), with or without autologous bone addition, for filling the cystic cavities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Traditionally, the left bony cavity can be regenerated through a programmed sequence of maturing steps without any fillings, starting with the blood clot 21 . Several researches have reported bone healing after enucleation and simple primary closure without bone grafts 10,22,23 . A computerized radiographic study showed a spontaneous increase of bone density of 7%, 27%, 46% after 2, 6, and 12 months, respectively 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the left bony cavity can be regenerated through a programmed sequence of maturing steps without any fillings, starting with the blood clot 21 . Several researches have reported bone healing after enucleation and simple primary closure without bone grafts 10,22,23 . A computerized radiographic study showed a spontaneous increase of bone density of 7%, 27%, 46% after 2, 6, and 12 months, respectively 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the oral cavity's high potential for self-regeneration of bone defects [16] , studies have demonstrated that patients not using any lling materials post-cystectomy exhibit a spontaneous bone healing index of only 12.34% [17] at six months post-surgery. Such results indicate that spontaneous bone healing is insu cient for complete bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…PRGF application should not be regarded as an alternative to conventional therapy (involving debridement of necrotic tissue), but as an adjunctive therapy [ 24 , 37 ]. PRGF was used in maxillofacial surgery to stimulate regeneration of osseous and epithelial tissues [ 25 , 38 ], in orthopedic surgery, sports medicine [ 39 ], arthroscopic surgery [ 40 ]. This innovative system also has application in anti-ageing since it stimulates the body’s own healing process for rejuvenation.…”
Section: ⧉ Discussionmentioning
confidence: 99%